A CRITICAL DISCOURSE ANALYSIS OF A TEXT ENTITLED “PAKISTANI GIRL SHOT BY TALIBAN CLAIMS TRIUMPH OVER TERRORISTS” USING VAN LEEUWEN’S 2009 METHOD - Euis Rina Mulyani (Eltin Journal : Journal of English Language Teaching in Indonesia, 2014)
This analysis was motivated by the previous studies which suggest that  texts  are never ideology-free nor objective; and  meanings are constructed through social languages or discourses  and are socially constructed,  not neutral and often privilege some while marginalizing or excluding others. The analysis was done to the text entitled  “Pakistani girl shot by Taliban claims triumph over terrorists”. The present analysis concerns: (1) the actions which are attributed to the participants in the text, (2) the participants’ actions which are de-agentialized and objectivated, (3) and the ideology behind the text. The text was analized by employing Van Leeuwen’s 2009 Method of Critical Discourse Analysis. Both qualitative and quantitative procedures were used to analyze the data. The conclusion of this study is that the ideology of egalitarianism or equalitarianism can strengthten its believers – even young believers – to fight agaist discrimination using various efforts including their verbal, physic, and  mental to get their rights. Key Words: Van Leeuwen’s method of Critical Discourse Analysis, Ideology